Converging wages, diverging GRP: Directed technical change and endogenous growth. Empirical analysis of growth patterns across Kazakh regions - Alisher Aldashev (Osteuropa-Institut Regensburg, 2011)
The paper analyzes unequal regional development in Kazakhstan. Applying the nonlinear least squares method in presence of spatial correlation we estimate the convergence rate of wages across Kazakh regions for the period 2003-2009. The estimated convergence rate is about 3% which is somewhat higher than estimates obtained for the USA and Europe. At the same time there is slight divergence in the GRP per capita. It is argued that convergence in wages which coincides with divergence in the per capita GRP is consistent with the endogenous growth model where profit maximizing firms choose the capital intensity of the technology. This implies that the inequality between regions will only exacerbate and the central government may wish to invest more in low-growth regions to alleviate disproportional development.
Keywords: O47; P25; P23; 330; convergence; endogenous growth; Kazakhstan; capital intensive technology; nonlinear least squares; spatial correlation; Regionale Entwicklung; Regionales Wachstum; Entwicklungskonvergenz; Lohn; Sozialprodukt; Neue Wachstumstheorie; Schätzung; Regionale Disparität; Kasachstan